Activated alumina as value-added byproduct from the hydrolysis of hierarchical nanoporous aluminum with pure water to generate hydrogen fuel. (August 2020) - Lee, Timothy; Fu, Jintao; Basile, Victoria; Corsi, John S.; Wang, Zeyu; Detsi, Eric
Abstract: The sale of value-added byproducts from hydrogen-generating reactions is a strategic approach to lower the costs of hydrogen fuel in order to realize a truly sustainable hydrogen economy. Metal hydrolysis is a chemical process that produces hydrogen together with a metal hydroxide species; however, this reaction is rarely observed without chemical additives or extreme reaction conditions. Previously, we demonstrated that hierarchical nanoporous aluminum can create hydrogen at standard conditions for temperature and pressure via hydrolysis without any additives. The advantage of this method is the co-production of pure aluminum hydroxide (Al(OH)3 ). Here we explore the transformation of this Al(OH)3 hydrolysis byproduct into valuable materials to elucidate strategies in reducing the overall cost of hydrogen generated. In particular, we demonstrate in this work that (i) the synthesis of hierarchical nanoporous aluminum is scalable to meet the needs of large-scale production for a hydrogen economy, and (ii) the Al(OH)3 hydrolysis byproduct can be transformed to create high surface-area "activated alumina" (Al2 O3 ) as a commercially viable product. Highlights: Co-production of hydrogen and activated alumina by hydrolysis of nanoporous aluminum. Large-scale processing of nanoporous aluminum. High-surface area activated alumina (∼161 m 2 /g) as a value-added byproduct from the hydrolysis of nanoporous aluminum.